2016
DOI: 10.1186/s13063-016-1215-6
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous magnesium sulfate for the management of severe hand, foot, and mouth disease with autonomic nervous system dysregulation in Vietnamese children: study protocol for a randomized controlled trial

Abstract: BackgroundOver the last 15 years, hand, foot, and mouth disease (HFMD) has emerged as a major public health burden across the Asia-Pacific region. A small proportion of HFMD patients, typically those infected with enterovirus 71 (EV71), develop brainstem encephalitis with autonomic nervous system (ANS) dysregulation and may progress rapidly to cardiopulmonary failure and death. Although milrinone has been reported to control hypertension and support myocardial function in two small studies, in practice, a numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The Vietnamese Ministry of Health HFMD Classification and Management Guidelines were used to stratify the severity of patients with brainstem encephalitis or encephalomyelitis [22]. Ataxia was considered a Grade 2b Group 2 criterion [16] (see Table S1, supporting information).…”
Section: Inclusion Criteria and Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Vietnamese Ministry of Health HFMD Classification and Management Guidelines were used to stratify the severity of patients with brainstem encephalitis or encephalomyelitis [22]. Ataxia was considered a Grade 2b Group 2 criterion [16] (see Table S1, supporting information).…”
Section: Inclusion Criteria and Definitionsmentioning
confidence: 99%
“…Outcomes according to the WHO clinical classification[21] and the Vietnamese HFMD classification[22] HFMD, hand-foot-mouth disease; IVIG, intravenous immunoglobulin; NRL, neurologic; mRS, modified Rankin Scale; WHO, World Health Organization. Differences were considered significant at p <0.05, and these values are listed in bold type.…”
mentioning
confidence: 99%
“…The study was approved by the ethics committees of HTD and the Vietnamese MoH, as well as the Oxford University Tropical Research Ethics Committee, and was carried out in strict compliance with all ICH-GCP guidelines and recommendations. The trial was registered with ClinicalTrials.gov (NCT01940250), and the full protocol has been published [23].…”
Section: Methodsmentioning
confidence: 99%
“…Inappropriate fluid resuscitation and acute kidney injury (AKI) may lead to FO in cases of severe HFMD. Limited studies have observed that hemofiltration is be an efficient rescue treatment in children with severe HFMD [9–11]. CRRT has been empirically used in patients with severe EV-A71-HFMD with cardiopulmonary failure since 2012 in our PICU.…”
Section: Introductionmentioning
confidence: 99%